2012
DOI: 10.1124/jpet.112.196543
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Regulation of ATP Binding Cassette Efflux Transporter Expression and Function in Microglia

Abstract: ATP-binding cassette (ABC) efflux transporters, including multidrug resistance protein 1 (Mdr1), breast cancer resistance protein (Bcrp), and multidrug resistance-associated proteins (Mrps) extrude chemicals from the brain. Although ABC transporters are critical for blood-brain barrier integrity, less attention has been placed on the regulation of these proteins in brain parenchymal cells such as microglia. Prior studies demonstrate that inflammation after lipopolysaccharide (LPS) treatment alters transporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 57 publications
2
35
0
Order By: Relevance
“…The fluorescent substrate calcein AM was used to characterize the transport activity of WT-MRP2 and variants in Flp-In 293 cells (18, 20). In brief, cell suspensions (prepared in medium, 500,000 cells/ml) were loaded with calcein AM (0.5, 2 or 10 μM) for 30 min at 37°C, 5% CO 2 ( uptake period ).…”
Section: Methodsmentioning
confidence: 99%
“…The fluorescent substrate calcein AM was used to characterize the transport activity of WT-MRP2 and variants in Flp-In 293 cells (18, 20). In brief, cell suspensions (prepared in medium, 500,000 cells/ml) were loaded with calcein AM (0.5, 2 or 10 μM) for 30 min at 37°C, 5% CO 2 ( uptake period ).…”
Section: Methodsmentioning
confidence: 99%
“…Inflammatory events may affect mRNA/protein expression of these transporters (57). For example, in vitro studies have shown that LPS-treated microglia express decreased mRNA/protein levels of several ABC transporters such as P-gp, Bcrp, Mrp2, Mrp4, and Mrp5 (58). Expression of these transporters indicates that microglia may play a role in CNS drug permeation and distribution; however, more studies are required to elucidate the role of microglia in drug uptake into the CNS.…”
Section: Components Of the Nvumentioning
confidence: 99%
“…We have observed that ACN accumulates more in astrocytes and it is known that these cells express CYP2E1 (Montoliu et al, 1995), however it is unknown whether microglia express CYP2E1. Additionally astrocytes and microglia express multidrug resistance-associated protein 1 (Mrp 1, ABCC1), an ATP-driven pump that mediates export of organic anions and GSH conjugates (Gibson et al, 2012; Mercier et al, 2004). Astrocytes are closely associated to the BBB, allowing for ACN –GSH conjugates to be removed from the brain by Mrp 1 or other related transporters.…”
Section: Discussionmentioning
confidence: 99%